2020
DOI: 10.17509/ije.v13i2.25340
|View full text |Cite
|
Sign up to set email alerts
|

Curriculum Implementation Facilitating and Hindering Factors: The Philippines Context

Abstract: This study focuses on the perceptions of Filipino teachers and school administrators of the different facilitating and hindering factors in curriculum implementations based on their practices and the challenges they have experienced. Using descriptive research employing quantitative design, 324 respondents were surveyed using self-made questionnaires anchored on Ecological System Theory (EST) by Bronfenbrenner (1979). The respondents from the grade school, junior high school, and senior high school expressed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…It is important to note that sampling could impact the data because of the limited sampled participants with higher/doctoral degree. Palestina and Pangan [22] conducted a study to determine the perceptions of teachers and school administrators facilitating curriculum implementation based on their practices and the challenges they have experienced. The findings revealed that the respondents who were from the higher grade and administrations manifested their understanding/agreement on the factors identified that facilitate curriculum implementation in the system/school.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that sampling could impact the data because of the limited sampled participants with higher/doctoral degree. Palestina and Pangan [22] conducted a study to determine the perceptions of teachers and school administrators facilitating curriculum implementation based on their practices and the challenges they have experienced. The findings revealed that the respondents who were from the higher grade and administrations manifested their understanding/agreement on the factors identified that facilitate curriculum implementation in the system/school.…”
Section: Resultsmentioning
confidence: 99%
“…The view of curriculum as a plan of action targets what works best in the classroom after considering the contextual challenges (Shoba, 2021). Researchers (for example, Salminen et al, 2016;Alvunger et al, 2021;Lin et al, 2015;Palestina et al, 2020) Thus, advocate for the inclusion of teachers in the planning and development process in order to facilitate the effective implementation of the curriculum. Zohar et al (2018) refer to the bottom-up dynamics (factors) as 'loose' because they have no specific and rigid structure that is followed by teachers during the enactment of curriculum.…”
Section: Bottom-up Dynamics (Societally-driven)mentioning
confidence: 99%
“…Teachers' instructional practices must align with the intended curriculum to ensure fidelity in implementing the science curriculum. Thus, curriculum implementation needs teachers' preparedness and dedication to accomplish the intended curricular outcomes (Palestina et al, 2020;Pandey, 2018).…”
Section: Introductionmentioning
confidence: 99%